23.2k views
3 votes
Just answer as quick as possible thank u

Just answer as quick as possible thank u-example-1
User Deck
by
6.1k points

1 Answer

5 votes
ANSWER

D. (-2,5)


Step-by-step explanation

The given equations are


8x + 5y = 9...(1)

and


y = x + 7...(2)


We substitute equation (2) into equation (1) to get,


8x + 5(x + 7) = 9


We expand the bracket to get,



8x + 5x + 35 = 9

Grouping similar terms, we obtain,



8x + 5x = 9 - 35

Simplify to get,

13x = - 26

Divide both sides by 13 to obtain,



x = - (26)/(13)



x = - 2



This implies that,



y = - 2 + 7


y = 5

The solution is (-2,5)
User Romario
by
6.5k points